(untitled) (Praxis Educativa, 2020)
The work focuses on education, social atomization and the terror of political authoritarianism and neoliberal fascism. Two different political tremors that shake the world these days are analyzed: on the one hand, the spread of resistance to the emerging neo-fascism; and on the other, a new emerence in massive forms of collective resistance against neoliberalism. The question lies about how education gives rise to ways of selftraining that can allow people to resist fascist and neoliberal mentalities. Pedagogy, as a resistance tool, opens a space for translation, criticism and resistance. This is particularly crucial in the face of atomization that isolates individuals and fosters a sense of helplessness by stating that the existing order cannot be changed. In order to dismantle these regimes, we must also find a way to break the atomization patterns that make them possible. Without hope there is no possibility of resistance, dissent and struggle. Organization is a condition for struggle, and hope is s condition for organization. Hope expands the space of the possible and becomes a way to recognize and name the incomplete nature of the present.